Social Comparison and Sharenting: Effects on Maternal Mental Health in the Digital Era - Dewani, Suci Windi; Elizabeth Kristi Poerwandari (Universitas PGRI Yogyakarta, 2026)
The rapid development of information technology, such as social media, can significantly impact daily life, including maternal mental health. Therefore, an overview of social media’s positive and negative impacts on maternal well-being is needed. This article presents a literature review of 7 articles, screened using the framework for narrative reviews method from Ferrari (2015), to explore the impact of social media use, including sharenting and social comparison, on maternal well-being. The reviewed literature includes studies involving mothers across diverse contexts, allowing for a broader understanding of the global impact on maternal well-being. The analysis found that social media development has both positive and negative impacts on maternal well-being. Positive impacts include easier access to information and social support. On the other hand, negative impacts involve social media use, increased depressive symptoms, and decreased life satisfaction, mainly due to pressure to fulfil ideal parenting standards. Keywords: housewives, intensive social media use, psychological distress